The Utility of Multimodal Imaging and Artificial Intelligence Algorithms for Overlying Two Volumes in the Decision Chain for the Treatment of Complex Pathologies in Interventional Neuroradiology—A Case Series Study - Bogdan Valeriu Popa; Aurelian Costin Minoiu; Catalin Juratu; Cristina Fulgoi; Dragos Trifan; Adrian Tutelca; Dana Crisinescu; Dan Adrian Popica; Cristian Mihalea; Horia Ples (Life, 2023)
3D rotational angiography is now increasingly used in routine neuroendovascular procedures––in particular, for situations where the analysis of two overlayed sets of volume imaging proves useful for planning the treatment strategy or for confirming the optimal apposition of the intravascular devices used. The aim of this study is to identify and describe the decision algorithm for which the overlay function of 3D rotational angiography volumes, high-resolution contrast-enhanced flat panel detector CT adapted for intravascular devices (VasoCT/DynaCT), non-enhanced flat detector C-arm volume acquisition functionality integrated with the angiography equipment (XperCT/DynaCT), and isovolumetric MRI volumes were all used in treatments performed in a series of 29 patients. Two superposed 3DRA volumes were used in the treatment aneurysms located at the junction of two vascular territories and for arteriovenous malformations with compartments fed from different vascular territories. The superposition function of a preoperatively acquired 3DRA volume and a postoperatively acquired VasoCT volume provides accurate information about the apposition of neuroendovascular endoprostheses used in the treatment of aneurysms. The automatic overlay function generated by the 3D workstation is particularly useful, but in about 50% of cases it requires manual operator-dependent correction, requiring a certain level of experience. In our experience, multimodal imaging brings an important benefit, both in the treatment decision algorithm and in the assessment of neuroendovascular treatment efficacy.